2018
DOI: 10.1111/jgh.14080
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐based scoring system for differential diagnosis of polypoid lesions of the gallbladder

Abstract: This ultrasound-based scoring system could be a useful means for differentiating between neoplastic and non-neoplastic gallbladder polyps in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
0
21
1
3
Order By: Relevance
“…The present study is not the only study to highlight the considerable overtreatment of gallbladder polyps, which underlines the need for improvements to ultrasound evaluation and patient selection for cholecystectomy for gallbladder polyps [20]. Multiple studies have outlined sonographic characteristics of gallbladder polyps that can be used to differentiate polyp type [6, 9-12, 21]. The most recent European guidelines have sought to incorporate this development partly by excluding definite nonneoplastic polyps prior to polyp size assessment based on “comet tail” artifacts, which can be seen in adenomyomatosis or cholesterol polyps [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is not the only study to highlight the considerable overtreatment of gallbladder polyps, which underlines the need for improvements to ultrasound evaluation and patient selection for cholecystectomy for gallbladder polyps [20]. Multiple studies have outlined sonographic characteristics of gallbladder polyps that can be used to differentiate polyp type [6, 9-12, 21]. The most recent European guidelines have sought to incorporate this development partly by excluding definite nonneoplastic polyps prior to polyp size assessment based on “comet tail” artifacts, which can be seen in adenomyomatosis or cholesterol polyps [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that more detailed sonographic characteristics could aid in the preoperative differentiation of polyp types [6, 9-12]. However, the most recent European guidelines do not advise on the characteristics that should be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…На УЗД поліп візуалізується як випинання, що виступає у просвіт жовчного міхура [16]. Старший вік, поодинокі утворення без ультразвукової тіні, з посиленим кровопостачанням, розмірами від 14-15 мм з широкою основою (понад 3,5 мм), конкременти чи осад в жовчному міхурі з високою ймовірністю вказують на неопластичний поліп жовчного міхура [20,21]. Частіше малігнізовані поліпи виявляються у жінок [22].…”
unclassified
“…Власне, проблема вибору правильної тактики при ПЖМ чітко залежить від його схильності до малігнізації. Хоча у 95 % випадків поліпи все таки є доброякісними, рак жовчного міхура є вкрай агресивною пухлиною з п'ятирічним виживанням менше 5 % [20]. Оскільки на доопераційному етапі складно визначитися з ймовірністю карциноми в жовчному міхурі, покази до холецистектомії індивідуалізують, базуючись, у першу чергу, на виділенні факторів ризику.…”
unclassified
See 1 more Smart Citation